Care Transitions. Issue 3 (July 2015) - Dusek, Brenda; Pearce, Nancy; Harripaul, Anastasia; Lloyd, Monique
<x xml:space="preserve">Abstract</x> This article reports results from a systematic review used to inform the development of a best practice guideline to assist nurses in understanding their roles and responsibilities in promoting safe and effective client care transitions. A care transition is a set of actions designed to ensure safe and effective coordination and continuity of care as clients experience a change in health status, care needs, health care providers, or location.